(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Haruki Murakami’s Hard-Boiled Wonderland and the End of the World constructs a perspective in which physical and psychological spaces unite, forming a map of the divided self. This paper explores how walls and labyrinths, recurring spatial motifs in the novel, reflect the limits and depths of human consciousness. The wall surrounding the “End of the World” embodies the mind’s impulse toward safety, order, and containment, an inner architecture protecting the self from external disorder. In contrast, the labyrinthine underworld of the “Hard-Boiled Wonderland” unfolds as a metaphor for the unconscious, a disorienting yet generative space where hidden memories and suppressed impulses surface in cryptic forms. These spaces are not merely backdrops but living metaphors of cognition, repression, and self-discovery. Through the protagonist’s passage between these contrasting realms, Murakami recasts space as a metaphor for the psyche, suggesting that identity itself is shaped by the fragile balance between control and chaos. The novel exposes the paradox of modern consciousness, confined by invisible walls of rational order and lost within the labyrinths of its own making. This paper approaches Murakami’s fiction as both a philosophical inquiry and a profoundly human journey that traces the search for identity amid the labyrinth of contemporary life.